Ответ:
1
Пошаговое объяснение:
1) 1 - cos4x = (sin 2x) ^ 2
2) tg(2x) = sin(2x) / cos(2x)
3) Получаем
![\frac{sin^2(2x)}{x sin(2x) : cos(2x)} = \frac{sin(2x)cos(2x)}{x} = \frac{sin(2x)}{2x} cos(2x) \frac{sin^2(2x)}{x sin(2x) : cos(2x)} = \frac{sin(2x)cos(2x)}{x} = \frac{sin(2x)}{2x} cos(2x)](https://tex.z-dn.net/?f=%5Cfrac%7Bsin%5E2%282x%29%7D%7Bx%20sin%282x%29%20%3A%20cos%282x%29%7D%20%3D%20%5Cfrac%7Bsin%282x%29cos%282x%29%7D%7Bx%7D%20%20%3D%20%5Cfrac%7Bsin%282x%29%7D%7B2x%7D%20cos%282x%29)
2x -> 0 при x -> 0, поэтому sin(2x)/2x -> 1.
Предел cos(2x) при x -> 0 равен cos(2*0) = cos(0) = 1.
Получаем, что предел всего выражения равен 1 * 1 = 1.